2009
DOI: 10.1136/adc.2007.136853
|View full text |Cite
|
Sign up to set email alerts
|

How common are rib fractures in extremely low birth weight preterm infants?

Abstract: The possibility of NAI should be considered in ex-ELBW infants found to have rib fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…In another series of VLBW infants, the prevalence of MBD was 40% in breastfed infants compared with 16% of those fed with a preterm formula supplemented with calcium and phosphorus 14 , 15 . A retrospective review of 72 ELBW infants who survived > 4 weeks between 1998 and 2002 revealed 7% (5/72) incidence of radiologically apparent rib fractures 16 . Mitchell et al, in a recent study (2006–2007), selectively screened 32 ELBW infants with ALP level > 800 IU/L for radiological rickets 4 .…”
Section: Discussionmentioning
confidence: 99%
“…In another series of VLBW infants, the prevalence of MBD was 40% in breastfed infants compared with 16% of those fed with a preterm formula supplemented with calcium and phosphorus 14 , 15 . A retrospective review of 72 ELBW infants who survived > 4 weeks between 1998 and 2002 revealed 7% (5/72) incidence of radiologically apparent rib fractures 16 . Mitchell et al, in a recent study (2006–2007), selectively screened 32 ELBW infants with ALP level > 800 IU/L for radiological rickets 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Posterior rib fractures, although rare and only in cases of difficult labour or large babies, have been reported after vaginal delivery [68]. Rib fractures are well described in metabolic bone disease of prematurity or other metabolic disorders and skeletal dysplasias [16, 59]. In these cases, rib fractures are seldom the only abnormal finding; family history, physical examination or the skeletal survey show indications for an underlying disorder or, e.g.…”
Section: Fracturesmentioning
confidence: 99%
“…Discerning abusive versus accidental rib fractures in extremely premature infants can be especially difficult. These infants are at higher risk for abuse given their special medical needs, but also are at increased risk for fractures secondary to osteopenia (45).…”
Section: Abdominal Traumamentioning
confidence: 99%